Envisioning the future: Does imagery help or hinder? - Beckett, K.; D.'Urso, J. (Mine Closure 2024: Proceedings of the 17th International Conference on Mine Closure, 2024)
As the saying goes, a picture says a thousand words. Across contexts, cultures and time, images share knowledge, inspire emotion, envision the future and build connections. But, as a means of communicating likely post-closure outcomes, are visualisations and images, including 3D visualisation, useful when pits and waste dumps have yet to be built and rehabilitation is likely to occur decades into the future? Visualisations of intended post-closure landscapes draw on various data sources as well as assumptions and creative imagination. These are often provided to stakeholders to inform, consult and, more recently, support joint decision-making about mine development, operations and post-mining landscapes. Generally, use of visualisations is seen as positive. Yet it comes with risks. While useful to increase awareness, undertake scenario planning and support discussion, these visualisations may not represent achievable outcomes or post-closure landscapes. There may also be differences in how individuals interpret visualisations. This creates a significant challenge. Visualisations are useful — and often needed — to enable stakeholders to provide guidance on preferred post-closure landscapes and future uses. And evidence of stakeholder input and consultation is required to secure regulatory consent to commence development. Furthermore, once a project begins, assumptions, environmental understanding, mining decisions and other factors that underpinned these visualisations may change. Even where the fundamentals of mining may not change, the aspects influencing visual amenity of landscape may. There is a risk they may live on only in the memory of stakeholders. This paper explores the pros and cons of using post-closure landscape visualisations as part of stakeholder engagement processes before operations cease. As we enter the artificial intelligence (AI) age – with more easily rendered artificial visualisations being flexible sources of fact – understanding and managing these pros and cons is critically important for transparent communications, ensuring informed consent and supporting respectful partnerships. It also recommends protocols on the provision and use of post-closure visualisations, in consideration of the confidence to deliver that outcome, to enable stakeholders to distinguish, at a glance, between the ambitious, the possible and the pragmatic.